Systematic Literature Review: The Impact of Coding Education on Computational Thinking Skills in Elementary School (2020-2025) - Okta Suphia Mawaddah; Mintarsih Arbarini; Bambang Subali3; Arif Widiyatmoko (Edu Cendikia: Jurnal Ilmiah Kependidikan, 2026)
Early coding education has been implemented in various elementary schools to improve digital literacy with relevant 21st-century skills. The main focus of competencies to be developed through coding education is computational thinking. This study aims to explore the impact of coding education on improving the computational thinking skills of elementary school students over the past five years. This study applied the Systematic Literature Review (SLR) method, searching for articles using Publish or Perish (PoP) software with Crossref as the data source. Bibliometric analysis was performed using VOSviewer to map publication trends, authors, citations, article sources, and research theme clusters. From a total of 1,000 identified articles, relevant publications were selected through a screening process based on the PRISMA protocol, resulting in 235 articles for further review and deeper analysis of coding education research trends related to the development of computational thinking in elementary school contexts. Coding education has been shown to positively develop computational thinking skills among elementary school students, especially fifth graders, although teaching methods and implementation context influence its effectiveness. This study provides an overview of research on coding and computational thinking education during 2020–2025 and identifies research gaps for further exploration in subsequent studies.